Analysis of sliding intensity in terms of removed volumes in the Tingoragra Creek, Huánuco district as contribution for risk evaluation - Javier Silva, Luz Alexandra (2019)
In recent years, the district of Huánuco has presented a population growth of 1.05%, through a forced settlement on unstable areas, increasing vulnerability to extreme events. The shape of the earth’s surface can be considered as resulting from an evolutionary system within time scales. Therefore, it is intended to analyze by means of digital image processing, mass removal volume using ALOS PALSAR satellite images (2006-2019) and Landsat 5 EMT and 8 OLI (1987-2018), to establish a relationship between the evolution of the landscape and the occurrence of landslides through topographic profiles. Finally, it was possible to demonstrate the difference between means of the evolution of the slide of the Tingoragra creek in the district of Huánuco (2006-2019), according to the intensity classification based on the volume by landslides (222,129,497 m³) to establish a risk analysis.